Nanomaterial effects on minimizing the local scour around bridge pier in curved channels - Ahmed H. Mahmoud; Anani E. Anani; Mamdouh A. Dardeer; Ahmed S. Habash (Water Science)
Local scour around bridge piers is considered one of the most common reasons for bridge failure. In this article, experiments were conducted using nanomaterial with non-cohesive soil to reduce scour around bridge piers in a curved channel with a 30-degree angle and radius long is 3.38 m. Three different diameters of piers were used: 4 cm, 5 cm, and 6 cm. The channel was made of transparent polycarbonate with a rectangular section (30 × 60 cm). It is 8 m long with a curved segment in the middle. Experiments were carried out under conditions of Froude’s number from 0.15 to 0.30, with five different portions of silica fume by weight and two types of mixes: dry and wet. A total of 120 experiments were conducted, including 12 using fine sand (D50) as a bed material reference. The experiments showed that the dry mix failed to produce significant results. The best result in reducing the scour depth (from 61% to 83%) was achieved with 8% silica fume in the wet mix. Compared to previous studies, it was found that the use of nanomaterials is efficient in reducing scour depth.